PENGARUH KOMPETENSI DOSEN DAN KUALITAS PELAYANAN TERHADAP MOTIVASI BERPRESTASI MAHASISWA - Karsadi, Ardi (Universitas Prof. Dr. Moestopo (Beragama), 2002)
The increasingly admission trend of new students in the school of communication science of the University of Dr. Moestopo (Religious) serious attention, especially for the quality services of learning process provided to the enrolled students. The hypothesis of this study was a positive relationship betweenboth the instructors competence and the schools service quality togetherwith the students achievement motivation seems to occur. The study results show that a positive correlation between instructors competence and students achievement motivation exists significantly with a correlation levelof0.228. Moreover, it is proved that a positive correlation be tween schools quality service and students achievement motivation occurs significantly with a correlation level of 0,228. Moreover it is proved that a positive correlation between schools quality service, together, and students achievement motivation with a correlation level of 0.264. The study also suggeststhat correlation contributions are 5.2 %; 5.5 %; and 7.0 %. Although the contributions are not so big, the test re sults show that they are significant enougl.